FACTORS AFFECTING THE UPTAKE OF VOLUNTARY HIV/AIDS COUNSELLING AND TESTING SERVICES IN THE WORKPLACE - Mundy, Janet Susan (My University, 2011)
Although there is some literature evidence of HIV/AIDS voluntary counselling and testing (VCT) research among high-risk groups, a review of the literature failed to identify research into the factors that support or undermine participation amongst workers in medium-sized enterprises. The purpose of this research was to fill this gap by identifying the factors affecting VCT uptake in such workplaces. An anonymous questionnaire was developed, piloted and applied at a medium-sized manufacturing company, yielding 370 (74%) fully completed responses. Observation and quantitative study results supported analysis of best practice intervention findings obtained via literature review and a qualitative study with workplace VCT experts. Perception of company support, proximity to people that have, or have died of HIV/AIDS, and VCT confidentiality were among factors found to have influenced uptake, but permanent employment status was the most significant factor associated with test participation. This research further indicated that workplace HIV/AIDS interventions must ensure that post-VCT benefits are understood, are accessible to all staff and their families, involve active employee representation, and seek to reduce the social and political barriers to HIV/AIDS care and support access if they are to be successful
MBA thesis - WBS
Keywords: HIV/Aids counselling; HIV/AIDS testing